Conformal atomic layer deposition of RuOx on highly porous current collectors for micro-supercapacitor applications. (3rd December 2022) - Choudhury, Sakeb Hasan; Vignaud, Guillaume; Dubreuil, Pascal; Assresahegn, Birhanu Desalegn; Guay, Daniel; Pech, David
Abstract: 3D porous electrodes have been considered as a new paradigm shift for increasing the energy storage of pseudocapacitive micro-supercapacitors for on-chip electronics. However, the conformal deposition of active materials is still challenging when highly porous structures are involved. In this work, we have investigated the atomic layer deposition (ALD) of ruthenium dioxide RuO2 on porous Au and Pt architectures prepared by hydrogen bubble templated electrodeposition, with area enlargement factors ranging from 400 to 10 000 cm 2 /cm 2 . Using proper ALD conditions, a uniform RuO2 coverage has been successfully obtained on porous Au, with a specific electrode capacitance of 8.1 mF cm −2 and a specific power of 160 mW cm −2 for a minute amount of active material. This study also shows the importance of the chemical composition and reactivity of the porous substrate for achieving conformal deposition of a ruthenium oxide layer.